2007
DOI: 10.1029/2007gl031903
|View full text |Cite
|
Sign up to set email alerts
|

Radar signatures of the urban effect on precipitation distribution: A case study for Atlanta, Georgia

Abstract: Ground‐based weather radar from Peachtree City, GA, is used to examine the distribution of summer precipitation in northern Georgia, including metropolitan Atlanta, during June–August of 2002–2006. The study included 194 “synoptically benign” days with a maritime tropical air mass type. Areas in eastern metropolitan Atlanta are shown to have 30% more rainfall during these days than areas west of the city. Both precipitation amount and frequency were enhanced up to 80 km to the east of the urban core of Atlanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(117 citation statements)
references
References 25 publications
7
107
0
3
Order By: Relevance
“…Factors influencing urban induced precipitation included low level moisture, urban heat island intensity, and atmospheric instability. Using ground-based weather radar, Mote et al (2007) showed that urban induced rainfall resulted in a 30% increase in rainfall in eastern metropolitan Atlanta, relative to the western metropolitan area [19]. The effects of urban induced rainfall could be measured up to 80 km to the east of the center of Atlanta.…”
Section: Montgomerymentioning
confidence: 99%
“…Factors influencing urban induced precipitation included low level moisture, urban heat island intensity, and atmospheric instability. Using ground-based weather radar, Mote et al (2007) showed that urban induced rainfall resulted in a 30% increase in rainfall in eastern metropolitan Atlanta, relative to the western metropolitan area [19]. The effects of urban induced rainfall could be measured up to 80 km to the east of the center of Atlanta.…”
Section: Montgomerymentioning
confidence: 99%
“…Results from METROMEX suggest that the urban effects lead to 5-25% increased precipitation, particularly 50-75 km downwind of the urban center during the summer months (Changnon et al, 1991). There is increasing evidence that urbanization and changes in urban-rural boundaries can have a significant feedback on the spatiotemporal patterns of precipitation (Shepherd et al, 2002;Shepherd and Burian, 2003;Niyogi et al, 2006;Mote et al, 2007;Lei et al, 2008). Cotton and Pielke (2007, Chapter 5;Pielke et al, 2007, Section 7) summarize numerous studies as to how urbanization alters rainfall patterns as a result of mesoscale circulations and through changes in convective available potential energy (CAPE).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, UHI can increase the rainfall in the vicinity of the cities. A number of studies have found an increase in rainfall in regions downwind of urban areas, with increases as high as 25 % in some cases (Shepherd et al, 2002;Mote et al, 2007).…”
Section: Introductionmentioning
confidence: 99%